Tipologi Pintu Dan Jendela Pada Fasad Rumah Di Kampung Biru Arema Kelurahan Kiduldalem - Nurtantyo, Muhammad Andi Finaldi (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2018)
One mindset about the development of thematic villages around the riverbank area (DAS) is aÂ bout the new paradigm coming from the Malang city government. Jodipan (KWJ) Colorfulkampong, 3D kampong (tridi), and White kampong in Klojen kampong can now be said to have been transformed because of this mindset. Currently there were new tourist villages,namely Kampung Biru Arema, which located in the Kiduldalem sub-district, which that had just been formalized and was in the process of being changed different with Jodipan, which has a variety of distinguished building color characteristics, Kampung Biru Arema only had one color that matches its name, which is blue. One of the characteristics that candistinguish between buildings with another to understand is the characteristics of the facade type a building. It can see these elements in the form of door and window opening elements. The purpose of this study was to identify the typology of doors and windows on the facades of houses in Kampung Biru Arema. The method used in this paper is a descriptive qualitative method, with a typology approach. The residential building is chosen as an object through the purposive sampling method. This study focused on the identification and analysis of door and window elements in house facades located in Kampung BiruArema RW.05 neighbourhood of Kiduldalem village, Malang city.Â DOI: https://doi.org/10.26905/lw.v10i2.2681